Effect of sowing time on productivity and thermal utilization of mustard (Brassica juncea) under sub-tropical irrigated conditions of Jammu - MEENAKSHI GUPTA; CHARU SHARMA; RAJEEV SHARMA; VIKAS GUPTA; M. K. KHUSHU (Journal of Agrometeorology, 2017)
Field experiments were conducted to study the effect of weather variability on mustard crop at Research Farm of Agromet Research Centre, SKUAST-J, Chatha, Jammu during rabi seasons of 2010- 11 to 2012-13. Treatments were comprised of three sowing dates (9th October, 24th October and 8th November) and two cultivars of mustard (RL-1359 and RSPR-01). The results revealed that days taken to physiological maturity and yield reduced significantly with delayed sowing. Mustard crop sown on 9th October utilised more thermal, and heat units as compared to 24th October and 8th November sown crops. The shortening of the duration of the crop sown late was due to forced maturity because of higher temperature during reproductive phase of the crop. Heat use efficiency (HUE) was found to be higher for earlier sown crop and it decreased with delay in sowing. Correlation studies indicated that lower night temperature during vegetative phase is favourable and higher day temperature during reproductive phase is not favourable for mustard yield.